PENTINGNYA MENGUASAI KOMUNIKASI BAHASA INGGRIS PADA MAHASISWA MANAJEMEN PEMASARAN - Kinanti Sekarningrum IKS (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
Abstract--For students majoring in English, it is clearly a major part of being able to communicate proficiently using English, but for non-English majors such as majoring in management, this is something that is not uncommon, even tends to be difficult for them. The problem that then arises is what learning techniques are appropriate and interesting for them to apply in order to be proficient, and how they apply the learning. Therefore, the research questions in this study are: (i) Why are English communication skills needed by students? (ii) what learning techniques are applied by management students? This study aims to: (i) find the mastery of English communication by law students (ii) learn learning techniques for management students to apply.Kata kunci: English Learning, Management Student, Communication Strategy